Spontaneous anion-exchange synthesis of optically active mixed-valence Cs2Au2I6 perovskites from layered CsAuCl4 perovskites. Issue 12 (14th January 2021) - Bhawna,; Roy, Mrinmoy; Vikram,; Borkar, Hitesh; Alam, Aftab; Aslam, M.
Abstract : Synthesis of Cs2 Au2 I6 by spontaneous anion-exchange from layered CsAuCl4 perovskite with superior optical properties and high absorption coefficient. Abstract : Cs2 Au2 I6, a lead-free photovoltaic material, has been synthesized via controlled and systematic addition of hydroiodic acid (HI) to CsAuCl4 . X-ray diffraction studies suggest the formation of Cs2 Au2 I6 when a threshold concentration of HI is added to CsAuCl4 . The final compound shows good stability against light, oxygen and moisture and at temperatures up to 140 °C without any phase degradation. The stability of Cs2 Au2 I6 is also confirmed by its high negative formation energy and the convex hull diagram constructed using Density Functional Theory (DFT). Absorption studies suggest an abrupt band shift from 2.31 eV to 1.06 eV when HI concentration reaches the threshold limit (∼100 μl). A sharp absorption edge was found for Cs2 Au2 I6 with an Urbach energy of 59 meV, indicating lower structural disorder and higher crystallinity.